The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1095/biolreprod.102.005694
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonicity-Induced Projections Reflect Cell Polarity in Mouse Metaphase II Oocytes: Involvement of Microtubules, Microfilaments, and Chromosomes1

Abstract: A previous study showed that with hypertonic sucrose treatment, a projection is formed in mouse metaphase II (MII) oocytes in proximity to the spindle and chromosomes, where a polarized cortical domain is located. However, little is known about the mechanisms involved in this process. Here, we designed a series of experiments to test the hypothesis that hypertonicity is the induction factor for the formation of projections in mouse MII oocytes. Our hypothesis was supported by the following evidence: 1) differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…The mitotic spindle of porcine oocytes also became disorganized after demecolcine treatment (Kawakami et al, 2003). Mouse oocytes are different from goat and bovine oocytes in that the actin-rich domains formed independent of demecolcine during oocyte maturation (Liu et al, 2002). In the present study, however, when goat oocytes were treated with demecolcine and CB in combination, the number of oocytes forming projections decreased significantly.…”
Section: Demecolcine-assisted Enucleation Of Goat Oocytes 197contrasting
confidence: 65%
“…The mitotic spindle of porcine oocytes also became disorganized after demecolcine treatment (Kawakami et al, 2003). Mouse oocytes are different from goat and bovine oocytes in that the actin-rich domains formed independent of demecolcine during oocyte maturation (Liu et al, 2002). In the present study, however, when goat oocytes were treated with demecolcine and CB in combination, the number of oocytes forming projections decreased significantly.…”
Section: Demecolcine-assisted Enucleation Of Goat Oocytes 197contrasting
confidence: 65%
“…It has been reported that the basic medium is not involved in induction of a cytoplasmic protrusion containing chromosomes in mouse oocytes using sucrose [22]. However, the effects of the basic medium on the phenomenon induced by demecolcine or in other species are unclear.…”
Section: Discussionmentioning
confidence: 98%
“…The cytoplasmic protrusion containing chromosomes in the mouse oocyte is considered to be induced by hypertonicity, the common role for sucrose in cryopreservation [24][25][26][27], because hypertonic solutions containing high concentrations of other sugars, such as maltose, trehalose, sorbitol, mannitol and glucose, or NaCl can also induce the same phenomenon [22]. Sucrose, which is unable to permeate through the plasma membrane, induces water molecules to move out of oocytes and, thus, effectively causes them to shrink.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations